TRUNK FUNCTION IN HEMIPLEGIC PATIENTS KINEMATIC ANALYSIS OF TRUNK BENDING AND GAIT PERFORMANCE (International Journal of Physiotherapy, 2016)
Background: Trunk function is considered important for stroke patients in rehabilitation, but the significance of this factoris unclear. In this study, we examined trunk function, defined as the ability to keep the trunk stable against gravity during movement. In addition, we aimed to elucidate the relationship between gait performance and trunk function.Methods: The subjects were 14 hemiplegic men and 20 healthy elderly men. Movement was assessed by a three-dimensional motion analysis system focusing on the trunk. The trunk was divided into three parts: the pelvis, the middle trunk, and the upper trunk. The parameters assessed were static standing, anterior tilt of the trunk in the standing position, and gait. We examined the relationship of each of these trunk movement factors with gait speed. All data was analyzed using SPSS program version 21 (p < 0.05).Results: Comparing data of hemiplegic patients to that of normal subjects, during trunk bending, a large rotation angle toward the non-affected side was found and that toward the affected side of the middle trunk at the toe off time of the affected limb during gait was found in hemiplegic patients (p < 0.01). The degrees of both rotation angles were related to the gait performance.Conclusion: The movement of the middle trunk during bending in hemiplegic patients affected gait performance. The results indicated that gravity and movements of lower limbs easily affected the middle trunk. This is an important factor to consider in the rehabilitation of hemiplegic patients.